2020
DOI: 10.1016/j.clnesp.2020.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and management of complications of venous access in home parenteral nutrition (HPN): A 19 year longitudinal cohort series

Abstract: Backgrounds and AimsLong term central venous access for Home Parenteral Nutrition (HPN) is associated with catheter related complications. The most studied and well known of these is Catheter Related Blood Stream Infection (CRBSI).This paper looks at other venous access complications, including blocked and damaged catheters, catheter related thrombosis and CRBSI. This paper will also present treatment outcomes for each of these complications. This paper will also examine if there are any correlating patient or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…As a result of heightened awareness and continuous efforts for infection prevention, rates of CLABSI have significantly improved 70,84,90–92 . Our study confirms that sepsis is the most important modifiable risk factor to prevent in‐hospital mortality in patients with SBS, and therefore, home PN programs should continue their efforts to maintain the lowest possible infection rates 93,94 …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As a result of heightened awareness and continuous efforts for infection prevention, rates of CLABSI have significantly improved 70,84,90–92 . Our study confirms that sepsis is the most important modifiable risk factor to prevent in‐hospital mortality in patients with SBS, and therefore, home PN programs should continue their efforts to maintain the lowest possible infection rates 93,94 …”
Section: Discussionsupporting
confidence: 63%
“…70,84,[90][91][92] Our study confirms that sepsis is the most important modifiable risk factor to prevent in-hospital mortality in patients with SBS, and therefore, home PN programs should continue their efforts to maintain the lowest possible infection rates. 93,94 Liver disease is also a common complication in patients with IF. 72 Studies have reported that abnormal levels of liver enzymes have been observed in many patients receiving home PN; however, specific diagnostic criteria for the diagnosis of IFALD is lacking, which has resulted in variability in the reported prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A low degree of heterogeneity at 23% ( P = 0.21) was seen in studies that used ALT and a moderate heterogeneity at 61% ( P < 0.01) in studies that only used systemic antibiotics. A sensitivity analysis performed by excluding the 2 studies ( 34 , 53 ) having <10 patients did not produce pooled salvage proportions that differed from those of the main analysis. Mixed-effects logistic regression analysis showed that the combination of systemic antibiotics with ALT was superior to systemic antibiotics alone (OR: 1.75; 95% CI: 1.21, 2.53; P = 0.003).…”
Section: Resultsmentioning
confidence: 84%
“…Most studies defined CRBSIs according to the CDC ( 17 , 35 , 39 , 43–45 , 52 ) or IDSA ( 15 , 16 , 31 , 32 , 36 , 50 ) guidelines; the other studies used either nonstandard definitions or did not report the definition used ( 33 , 34 , 37 , 41 , 48 , 49 , 51 , 53 , 54 ). Two studies reported a slightly modified definition, but were still considered as appropriate and were counted as using the CDC definition ( 24 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation